Investigation of the Mechanism of Conductivity of NbN Thin Films, Modified Under Composite Ion Beam Irradiation - Gurovich, B. A.; Prikhodko, K. E.; Tarkhov, M. A.; Domantovsky, A. G.; Komarov, D. A.; Goncharov, B.V.; Kuleshova, E. A. (Micro and Nanosystems, 2015)
The paper considers the use of low-energy composite ion beam radiation to change the superconducting properties of ultrathin (5 nm) films of niobium nitride. It was found that the effect of ion irradiation causes a reduction in the superconducting transition temperature and increasing the resistivity of the film in the normal state. We studied the electrical properties of the irradiated films with doses up to 12.6 d.p.a. (for Nitrogen) in the temperature range from 2 to 300 K. It is found that at a temperature of 4.2 K films irradiated with doses of 12.6 d.p.a. and above showed electric conductivity mechanism corresponding to typical insulators, and irradiated in a dose range 1.8-9 d.p.a. exhibited electrical conductivity mechanism corresponding to metals. We considered the possibility to use the technique of selective changes in the atomic composition under ion beam irradiation to create the resistive elements for cryogenic temperatures.
Keywords: niobium nitride thin films